Fabricated (Mawduʿ) Hadiths in Tafsir bi al-Ma’thur: A Study of Tafsir al-Kashf wa al-Bayan, al-Jami’ li Ahkam al-Qur’an, and Fath al-Qadir - Cima Ghoziah; Uswatun Hasanah (Universitas Muhammadiyah Enrekang, 2025)
This study investigates the presence of fabricated (maudu‘) hadiths within selected classical tafsir works. Utilizing a descriptive-analytical method and a library research approach, the analysis focuses on two main cases: (1) the narration concerning the virtues of Qur’anic surahs in al-Kasyf wa al-Bayan by as-Sa‘labi and (2) the narration about the movement of Iblis in al-Jami‘ li Ahkam al-Qur’an by al-Qurtubi. The findings demonstrate that both narrations fall into the category of fabricated or extremely weak traditions in terms of their chains of transmission (sanad) and textual content (matan), yet they were still cited by classical exegetes without adequate critical evaluation. Contributing factors include the tendency to compile all available narrations without rigorous scrutiny, limited access to authoritative sources during the period of tafsir compilation, and a cautious attitude toward criticizing potentially sensitive narrations. The study concludes that fabricated hadiths, as a form of ad-dakhil in the bi al-ma’sur exegetical tradition, can obscure the accurate understanding of Qur’anic verses.